2016
DOI: 10.1038/ncomms13643
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a new type of topological Weyl fermion semimetal state in MoxW1−xTe2

Abstract: The recent discovery of a Weyl semimetal in TaAs offers the first Weyl fermion observed in nature and dramatically broadens the classification of topological phases. However, in TaAs it has proven challenging to study the rich transport phenomena arising from emergent Weyl fermions. The series MoxW1−xTe2 are inversion-breaking, layered, tunable semimetals already under study as a promising platform for new electronics and recently proposed to host Type II, or strongly Lorentz-violating, Weyl fermions. Here we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
115
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 184 publications
(121 citation statements)
references
References 61 publications
6
115
0
Order By: Relevance
“…I. Belopolski et al [73] demonstrated in Mo x W 1-x Te 2 that a group of WPs were at the Fermi level as shown in Figure 5, making Mo x W 1-x Te 2 a promising platform for transport and optics experiments on Weyl semi-metals. H. Zheng et al [74] visualized the interference pattern on Mo 0.66 W 0.34 Te 2 by atomic resolution scanning tunnelling microscopy and spectroscopy (STM-STS).…”
Section: Approaching the Weyl Pointsmentioning
confidence: 99%
“…I. Belopolski et al [73] demonstrated in Mo x W 1-x Te 2 that a group of WPs were at the Fermi level as shown in Figure 5, making Mo x W 1-x Te 2 a promising platform for transport and optics experiments on Weyl semi-metals. H. Zheng et al [74] visualized the interference pattern on Mo 0.66 W 0.34 Te 2 by atomic resolution scanning tunnelling microscopy and spectroscopy (STM-STS).…”
Section: Approaching the Weyl Pointsmentioning
confidence: 99%
“…For example, both the carrier doping and external pressure are known to engineer the Fermi surface of these compounds (e.g., Refs. 10,44,[48][49][50].…”
mentioning
confidence: 99%
“…Further transport measurements have revealed unconventional magnetic and optical responses of TaAs family [26][27][28][29]. Despite recent advances of topological semimetals in both theory [30][31][32][33][34][35][36][37][38][39][40][41][42][43] and experiment [26][27][28][29][44][45][46][47][48][49][50][51] , the ferromagnetic Weyl semimetal [8,9,[52][53][54][55][56][57] has not been realised in experiments. A key issue is that first-principles band structure calculations on these magnetic materials (e.g.…”
mentioning
confidence: 99%